Clinical characteristics and outcomes of adult patients admitted with COVID-19 in East London: a retrospective cohort analysis. Issue 1 (17th March 2021) - Cheng, Daryl; Calderwood, Claire; Skyllberg, Erik; Ainley, Adam
Abstract : Background: Descriptions of clinical characteristics of patients hospitalised withCOVID-19, their clinical course and short-term inpatient and outpatient outcomes in deprived urban populations in the UK are still relatively sparse. We describe the epidemiology, clinical course, experience of non-invasive ventilation and intensive care, mortality and short-term sequelae of patients admitted to two large District General Hospitals across a large East London National Health Service Trust during the first wave of the pandemic. Methods: A retrospective analysis was carried out on a cohort of 1946 patients with a clinical or laboratory diagnosis of COVID-19, including descriptive statistics and survival analysis. A more detailed analysis was undertaken of a subset of patients admitted across three respiratory units in the trust. Results: Increasing age, male sex and Asian ethnicity were associated with worse outcomes. Increasing severity of chest X-ray abnormalities trended with mortality. Radiological changes persisted in over 50% of cases at early follow-up (6 weeks). Ongoing symptoms including hair loss, memory impairment, breathlessness, cough and fatigue were reported in 70% of survivors, with 39% of patients unable to return to work due to ongoing symptoms. Conclusions: Understanding the acute clinical features, course of illness and outcomes of COVID-19 will be crucial in understanding the effect of differences in risk, as well as the effectiveness of new interventions and vaccination between the successive waves of the pandemic.